2015
DOI: 10.1038/ncomms9292
|View full text |Cite
|
Sign up to set email alerts
|

The outer mucus layer hosts a distinct intestinal microbial niche

Abstract: The overall composition of the mammalian intestinal microbiota varies between individuals: within each individual there are differences along the length of the intestinal tract related to host nutrition, intestinal motility and secretions. Mucus is a highly regenerative protective lubricant glycoprotein sheet secreted by host intestinal goblet cells; the inner mucus layer is nearly sterile. Here we show that the outer mucus of the large intestine forms a unique microbial niche with distinct communities, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
356
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 412 publications
(385 citation statements)
references
References 69 publications
17
356
0
2
Order By: Relevance
“…1, we found that the adherent mucus of germ-free (GF) mice was only ∼25% as thick as that of SPF mice in vivo (Fig. 4B), consistent with previous observations (8,32). Thicker SPF mucus was previously attributed solely to altered mucus secretion by the host in response to the presence of microbes, and not to the difference in polymeric composition of the gut fluid.…”
Section: Applied Physical Sciencessupporting
confidence: 90%
“…1, we found that the adherent mucus of germ-free (GF) mice was only ∼25% as thick as that of SPF mice in vivo (Fig. 4B), consistent with previous observations (8,32). Thicker SPF mucus was previously attributed solely to altered mucus secretion by the host in response to the presence of microbes, and not to the difference in polymeric composition of the gut fluid.…”
Section: Applied Physical Sciencessupporting
confidence: 90%
“…Human gastrointestinal mucus consists of two layers, a thick loosely mucus layer and a thinner layer attached to the mucosa (35). While the inner layer is nearly sterile, the outer mucus layer forms a microbial niche that also includes nonmucolytic bacteria (36,37). One of those bacterial species is E. coli (38).…”
Section: Figmentioning
confidence: 99%
“…Although various plausible hypotheses could explain how the mutations discussed above could be selected in extraintestinal virulence compartments, the human gut itself is a highly dynamic and compartmentalized environment, with oscillating nutrient composition and other physiological conditions (72,73). This could allow adaptive diversification within resident strains via many different mechanisms, including gene inactivation.…”
Section: Discussionmentioning
confidence: 99%